All-optical multifunctional logic operations using simultaneously both interferometric output ports in a symmetric SOA-MZI - Reis, Cláudia (2015)
In this paper, all-optical logic functions, implemented with a single SOA-based Mach-Zehnder interferometer (SOA-MZI), are demonstrated experimentally and through numerical simulations. The proposed optical configuration is capable to carry out four logic operations, using simultaneously both output ports of the SOA-MZI. This may reduce the power cost and make possible to obtain simultaneously multi logic functions. The performance of such architecture is assessed measuring the obtained extinction ratio (ER) for each Boolean function. The potential of integration makes the proposed scheme attractive to perform optical signal processing operations in next generation photonic transmission systems.